Ocenjevanje števila in velikosti gospodinjstev - Jakoš, Aleksander (Urbani izziv, 1995)
The article deals with the methodology of calculation of the future number of households by number of members by age and sex structure of the population calculated from population projections. Due to decrease in the average size of households, and other reasons, the number of households is growing faster than the population. A mathematical calculation matrix is also added.
Keywords: demografska statistika; demografska struktura; gospodinjstva; metodologija; Slovenija